Pelatihan Penulisan Karya Ilmiah bagi Guru-Guru MTS dan MA Ulumiyyah Tuban - Rini Damayanti; Kaswadi Kaswadi; Agung Pranoto (LPPM Universitas Flores, 2021)
The Community Service Program (Penmas) which is carried out aims to increase the willingness of teachers to write scientific papers, increase the ability of teachers to write scientific papers, and improve the ability to search for references in various sources. The implementation of Penmas was preceded by providing information to the Principal about the training activities to be carried out, giving invitations to teachers who would be training participants, conducting training 15 February 2021 virtually, and making reports on the results of the implementation of activities. The materials presented during the training are: 1) the urgency of writing scientific papers for career advancement and knowledge of educators, 2) strategies for writing scientific proceedings and journals, 3) systematic proceedings and journal articles. Participants also received guidance on writing scientific papers in tutorial activities and practicing writing scientific papers virtually. Training participants are limited to 40 MTS and MA Ulumiyyah Tuban teachers.